Resource nationalism meets the market: Political risk and the value of petroleum reserves - Click, Reid W; Weiner, Robert J (Journal of International Business Studies, 2010)
This paper investigates the effect of resource nationalism on the value of petroleum (crude oil and natural gas) reserves. We develop a framework for treating resource nationalism as political risk, and utilize data on reserve transactions (from John S. Herold) and political risk ratings (from International Country Risk Guide and Institutional Investor) for the period 2000–2006. Controlling for other factors that affect reserve value, we demonstrate the value destruction of political risk, and estimate the political risk discount for 37 countries. The paper contributes to both the international business literature and practitioner approaches to political risk analysis in demonstrating use of publicly available market data from real-asset transactions to measure the cost of political risk. We also show that the discount depends on market conditions: the higher expected future petroleum prices are, the larger is the discount at any level of political risk. This insight adds a new dimension to analysis of political risk, which is typically measured and examined without regard to market conditions.